The weightage of environmental elements for Malaysia state green road index of rural area - Nurul Ashikin Shuhaimi; Noraziah Hamid; Rozana Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2022)
“Green road” is a concept introduced to meet the requirements of economic, societal, and environmental aspects in road construction and its operation. Towards the responsive efforts of sustainable development, many countries had established their environmentally friendly green road assessment tools including for highways and roads. However, the application of the tools is somehow limited to specific project life cycle such for design and planning assessment and/or only for the higher cluster of the road such as toll road or federal highway, but rarely focus on road in rural area. This paper therefore aims to identify the appropriate environmental criteria and elements as proposal for Malaysia State Road Index for the rural area. The weightage of environmental elements for the Malaysia State Road Index for the rural area was established in the discussion of this paper. The environmental criteria and elements were reviewed via critical literature review of content analysis were of ‘green tools’. The confirmation of weightage was conducted via questionnaires development and responded by the focus group discussion (FGD) and validation survey. The FGD were the experts involved in road infrastructure development. The data is analysed using the Statistical Package for the Social Sciences (SPSS) software. This study discovered ten sub-criteria and thirty-three elements under ‘green road’ of significant environmental sustainability elements. The result showcases a fair distribution of weightage for each element within their sub-criteria.